The Important Game-Related Statistics for Qualifying Next Rounds in Euroleague - Ilkay Dogan; Yasin Ersoz (Montenegrin Sports Academy, 2019)
Euroleague is one of the most popular professional indoor sports leagues in the world. It is globally ranked as the fi ft h-highest professional indoor sports league and the second-highest professional basketball league, just trailing behind the National Basketball Association (NBA). Th e objective of this study was to determine which game-related statistics can assist in predicting the team that will qualify for the next rounds of the Euroleague. Th e data used in the study were obtained from each team's offi cial average box score on the Euroleague website for 2010-2017. Th e datasets were arranged into two groups depending on the qualifi cation of the teams into the subsequent round. Discriminant analysis was applied to fi nd the gamerelated statistics that better contribute to qualifying for the next round. A three-point fi eld-goal percentage was considered to be an essential variable in every round. However, it was also observed that, contrary to expectations, off ensive rebounds had a negative eff ect in the fi nal four rounds. It is recommended these results be used to plan the team strategies and the player strategies accordingly in a long-term and demanding tournament like Euroleague.